[68Ga] labelled Exendin for radioguided surgery of intrapancreatic insulin producing lesions in patients with congenital hyperinsulinism - Peter Kühnen; Sonal Prasad; Karin Rothe; Kai Huang; Kathrin Hauptmann; Marti Boss; Nicola Beindorff; Erwin Lankes; Steven W. Warmann; Miriam Schneider; Paniz Akbarzadeh Taghavi; Lara Lechner; et al. (EJNMMI Research)
Abstract Background Congenital hyperinsulinism (CHI) is a life threatening disease. Localization of affected intrapancreatic beta cells responsible for focal forms during surgery can be challenging. In this study we investigated a new radioguided surgical (RGS) approach using [68Ga]Exendin to facilitate intraoperative focus detection. All patients were scanned initially with [18F]-DOPA-PET followed by [68Ga]Exendin PET to differentiate between focal and non-focal forms. Focal CHI patients were then operated. At the beginning of standard surgical dissection of the pancreas in CHI patients (n = 12), 46 MBq of [68Ga]Exendin were injected intravenously. Intrapancreatic localization of the foci was determined by using a hand-held positron- and gamma-radiation probe. RGS was carried out as enucleation of CHI foci. Duration of surgery (defined as the time lapse from first incision until final suture placement) for RGS was compared with historical data of patients operated on without RGS. Long term follow-up data on euglycemic control were retrieved from patient´s medical files. Results [18F]-DOPA- and [68Ga]Exendin PET findings were concordant in all patients. Overall, 12 CHI patients underwent RGS. In 11/12 children (92%) the CHI foci localized pre-operatively by [68Ga]Exendin PET could be detected intraoperatively using the hand-held positron probe. There was a high correlation between PET imaging results and positron probe findings in respect to the identification of the affected pancreatic region. One pancreatic lesion in close proximity to the left kidney could not be detected by the positron probe. Histopathology confirmed all resected lesions as CHI foci. Intraoperatively, the signal of the focus was > 10 times higher than the signal of normal adjacent pancreatic tissue. Median duration of surgery was 4.7 h (CI 3.5–6.7) in RGS patients compared to 5.5 h (CI 4-6.7) in patients undergoing surgery without radio guidance. All patients remained euglycemic after surgery (median follow-up 3 years, range 2 to 4.5). Conclusions In this study, we demonstrated the use of [68Ga]Exendin for intraoperative localization of intrapancreatic CHI foci. RGS facilitates localization of intrapancreatic CHI focus and thus potentially reduces duration of surgery and perioperative complications.